Periodesasi Perkembangan Studi Hadits (Dari Tradisi Lisan/Tulisan Hingga berbasis Digital) - Luthfi Maulana (ESENSIA: Jurnal Ilmu-Ilmu Ushuluddin, 2016)
The history of the study of hadith from time to time experiencing a very significant development, beginning the study of hadith from oral to oral evolved into writing changes by others as a form of concern about the loss of traditions of the Prophet Muhammad, the development of tradition reached its peak when entering the period of the Successors exactly rule caliph Umar bin Abdul Aziz, where the tradition at this time officially codified in order to cope with the spread of false traditions pioneered by the heretics. Furthermore, after the tradition codified development be very rapid, with the birth of the canonical books of hadith to appear the terms scholarly tradition oriented as selectors hadith (criticism sanad hadith) and there are also books Sharh hadith as explanatory traditions of the Prophet Muhammad, Until the next period the study of hadith switch does not just dwell on criticism sanad but has entered the criticism of honor. In fact, along with the times that has entered the digital age, tradition began in containers therein to present assessment traditions more easily.[Sejarah kajian hadis dari masa ke masa mengalamai perkembangan yang sangat signifikan, mulanya kajian hadis dari lisan ke lisan berkembang menjadi tulisan, perubahan tersebut tak lain sebagai bentuk kekhawatiran akan hilangnya hadis-hadis Nabi SAW, perkembangan hadis mencapai puncaknya ketika memasuki periode tabiin tepatnya pemerintahan khalifah Umar bin Abdul Aziz, dimana hadis pada masa ini resmi dikodifikasi guna menanggulangi tersebarnya hadis-hadis palsu yang di pelopori oleh para pelaku bid’ah. Lebih lanjut, setelah hadis dikodifikasi perkembanganya menjadi sangat pesat, dengan lahirnya kitab-kitab kanonik hadis hingga muncul term-term keilmuwan hadis yang berorientasi sebagai penyeleksi hadis (kritik sanad hadis) serta muncul pula kitab-kitab syarh hadis sebagai penjelas hadis-hadis Nabi SAW. Hingga periode selanjutnya kajian hadis beralih tidak hanya berkutat pada kritik sanad melainkan sudah memasuki kritik terhadap matan. Bahkan seiring dengan perkembangan zaman yang sudah memasuki era digital, hadis mulai di kemas di dalamnya guna mengdirkan pengkajian hadis dengan lebih mudah.]